Improving production planning and scheduling processes at an Industrial/Agricultural Chain Manufacturer - Tandon, Ramit (2008)
A key question which every manufacturing firm, irrespective of its scale faces is about deriving an appropriate production planning and control mechanism that enables it to effectively cater to the market demand along with improving profitability. This project looks at applicability of Material Requirement Planning, Just in Time and Theory of Constraints as production planning and control mechanisms with a specific focus on applying them at Renold Chain Plant in Bredbuy, Stockport, Manchester. RenoldÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¾ÃÂ¢s plant although maintaining its competitive advantage faces certain operational obstacles such as considerable order backlogs and high levels of work in progress. The adverse effect of these is further accentuated by a high degree of complexity in the production process and a huge variety of part numbers produced. Due to a combined effect of all these factors the desired levels of throughput are not achieved. To make the analysis systematic and as structured as possible, initially relevant people from all departments involved in production and order managing were interviewed. This gave various perspectives on the existing issues and possible suggestions. A conscious effort was made to connect all the different issues to identify a core problem area using TOC ÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡Ãâ¹Ãâthinking processÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¾ÃÂ¢ tools. Following this, potential causes for this areaÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¾ÃÂ¢s supposed ÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡Ãâ¹ÃâunderÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¾ÃÂ¢ performance have been identified using a fish bone analysis. Finally, connecting the findings with the relevant literature researched, two customised ÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡Ãâ¹ÃâhybridÃÆÃâÃâ Ã¢â¬â¢ÃÆÃ¢â¬Å¡ÃâÃÂ¢ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¡ÃÂ¬ÃÆÃâÃÂ¢Ã¢âÂ¬ÃÂ¡ÃÆÃ¢â¬Å¡ÃÂ¢Ã¢â¬Å¾ÃÂ¢ production planning and control mechanism have been developed to enable Renold improve order management. These hybrids include appropriate aspects picked up from MRP, JIT and TOC. Furthermore, a series of prerequisite suggestions have been made which are required and would also compliment any change implementation brought about at the Bredbury Plant. The analysis was also presented to management at Bredbury in the form of a power point presentation and a brief feedback is given at the end.